Determinar la presencia de Toxocara canis en perros en el sector El Moral del cantón la Maná mediante la técnica de flotación - Llumiluisa Noble, Carlos Daniel (2025)
Toxocara canis is an intestinal nematode that mainly affects dogs, especially puppies. This parasite is of both veterinary and zoonotic importance, as it can cause diseases in humans such as visceral and ocular larva migrans. In dogs, it is located in the small intestine, where adults feed on intestinal contents. The eggs of this nematode are eliminated in the feces, contaminating the environment and developing under favorable conditions until reaching its infective stage. Transmission can occur by ingestion of larvae, transplacentally or lactogenically. A study of 50 fecal samples was carried out using the flotation method with saturated solution, from which a prevalence of 30% of 15 positive cases and 70% of 35 negative cases of Toxocara canis was obtained. The ages of greatest affectation were those under one year, which is why in the present work it had statistical significance.